Temporal Patterns of Shrub Vegetation and Variation with Precipitation in Gurbantunggut Desert, Central Asia - Yuguang Yang; Chengyi Zhao; Ming Han; Yike Li; Ruihong Yang (Advances in Meteorology)
The relationship between shrub vegetation and precipitation is one important component of desert vegetation responses to climate change, but it has not been understood completely because of its complexity and nonlinearity. In this study, we used MODIS NDVI data and precipitation data from 2004 to 2012 to evaluate the relationship between the shrub vegetation and precipitation within Gurbantunggut Desert, Central Asia. Correlation analysis was employed to explore the relationship between NDVI and precipitation within growing season, within cross growing season, and on interannual scale. The results showed that NDVI could be classified into three temporal changing patterns within growing season, and NDVI was significantly correlated with the precipitation integrated by time durations and time lags within growing season; NDVI was significantly correlated with precipitation in the early growing season, but this relationship was not so obvious in the middle or late growing season; and the NDVI variational patterns depended on mean annual precipitation and the distribution of precipitation throughout the year. Precipitation had significant influence on shrub vegetation within Gurbantunggut Desert. Our findings provide basic knowledge for the relationship between precipitation and shrub vegetation, and it is helpful to understand how the desert vegetation responds to climate change in the future.